Metal‐Organic Frameworks as curing accelerators for benzoxazines. Issue 13 (30th August 2016) - Sharma, Pratibha; Srivastava, Manju; Lochab, Bimlesh; Kumar, Devendra; Ramanan, Arunachalam; Roy, Prasun Kumar
Abstract: Benzoxazine resins, although exhibiting attractive properties; particularly high thermal stability and near zero‐ shrinkage, suffer from a major drawback associated with its high curing temperature. In view of the Lewis acidity associated with the Zn4 O nodes in a zinc based metal organic framework [Zn4 O(BDC)3, MOF5], we considered it of interest to explore its potential as a curing accelerator for a representative biobased benzoxazine resin. MOF 5 was solvothermally synthesized and characterized using different techniques including powder X‐ray diffraction (PXRD), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), Fourier transform infrared spectroscopy (FT‐IR) and Nitrogen physisorption measurements. Bio‐based benzoxazine resin was synthesized by mannich type condensation of cardanol and aniline with formaldehyde under solventless conditions, the structure of which was confirmed using FT‐IR and 1 H‐NMR. The curing behavior of the synthesized resin was systematically investigated using non‐isothermal Differential Scanning Calorimetry (DSC). Introduction of MOF 5 led to a shift in the curing profile to lower temperature, the extent of which was proportional to the amount of MOF 5 in the formulation. DSC studies were performed at different heating rates to establish the kinetic parameters associated with the curing of the resin. Activation energy, as calculated using Kissinger Akahira Sunose method, was found to concomitantly decrease from 98 kJ/mol to 58 kJ/mol upon addition of MOF 5 (5 % w/w). Abstract : The potential of MOF 5, an archetypal robust three dimensional zinc carboxylate framework [Zn4 O(BDC)3 ], as an accelerator towards curing of benzoxazine resin is demonstrated. The polymerisation of benzoxazine in the presence of MOF 5 proceeds through the coordination of the Zn4 O cluster with the benzoxazine moiety resulting in formation of polybenzoxazine with phenolic structures. It is the Lewis acidity associated with the Zn4 O nodes, which is responsible for this pronounced ability.